THE EFFECT OF SHOPPING MOTIVES AND STORE ATTRIBUTES TOWARD SHOPPING EXCITEMENT AND SATISFACTION AT MULTINATIONAL HYPERMARKETS IN INDONESIA - ASEP HERMAWAN; FARIDA JASFAR (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2004)
This study investigated the effects of shopping motives and store attributes toward shopping excitement and satisfaction at multinational hypermarkets in Indonesia markets. Among three types of shopping motives (socialization, utilitarian and diversion), utilitarian significantly affected shopping excitement. Excitement positively affected satisfaction. The results of this study have important implications for local as well as multinational retailers and also for further research in global retailing.